Persepsi Masyarakat terhadap Dampak Sosial Ekonomi Rencana Pembangunan Jembatan Selat Sunda - Suriadi, Andi; Mahida, Masmian; Lestari, Aldina Rani (Jurnal Sosial Ekonomi Pekerjaan Umum, 2015)
Construction of Sunda Strait Bridge is expected as the main infrastructure to support national connectivity, particularly Java – Sumatera. Several studies on physical-technical aspects asses that Sunda Strait Bridge is decent built. To support this, the study of non technical aspect especially perceptions on the socio-economic impact is needed. This study aims to determine the perceptions of local people towards socio-economic impacts if JSS is built. Thus, a planned and systematic step in minimizing potential adverse impacts can be done. Using quantitative approach, the survey was conducted on 7 districts in South Lampung Regency by taking 100 respondents in various circles. The result shows that if the bridge is built: (a) migration from Java to Sumatera (77%) and migration from rural to urban (58%); (b) conversion of paddy land/farm to industry (63%) and to settlements (53%); (c) ownership changes of local residence to businessman (67%) and to migrants (71%); (d) business opportunity trade (89%), service industry (89%), goods industry (86%); (e) excess of construction: pollution (65%), traffic congestion (28%), slum (35%), crime (62%), and prostitution (32%). Consider the variations of the impact, it recommends to make a local regulation to protect land ownership and land use, and to optimize positive impact the construction of Sunda Strait Bridge.